Chronic kidney disease screening and associated factors among people living with HIV on anti-retroviral therapy in Dar Es Salaam, Tanzania: Hospital-based cross-sectional study - Magreth Theophil; Ally Abdul Lyimo; Joel Seme Ambikile (PLoS ONE, 2026)
Background Chronic Kidney Disease (CKD) is a significant global health challenge, particularly among people living with HIV (PLHIV) on antiretroviral therapy (ART). The combined effects of HIV infection, long-term ART exposure, and other comorbidities increase CKD risk in this population. Despite international and national recommendations for routine CKD screening, the uptake remains inconsistent in resource-limited settings like Tanzania. Understanding the prevalence and associated factors of CKD screening is vital for improving early detection and patient outcomes. This study aimed to determine the prevalence of CKD screening and associated factors among PLHIV on ART in Dar es Salaam, Tanzania. Methods This was a hospital-based cross-sectional study conducted in Dar es Salaam, Tanzania. Data were collected using a semi-structured questionnaire and the review of medical records. A systematic random sampling method was used to recruit participants in the study. Descriptive analysis was used to summarize participants’ characteristics and the prevalence of CKD screening. Univariate and multivariate logistic regression were applied to identify factors associated with CKD screening, with a p-value < 0.05 considered for statistical significance. Results Among 426 adults on ART, CKD screening uptake was high (94.1%). Screening was more likely among participants with higher CD4 counts (>350 cells/µL; AOR: 9.73, 95% CI: 1.21, 78.16; p = 0.032), and less frequent ART clinic attendance was associated with lower screening odds (every six months vs. monthly; AOR: 0.16, 95% CI: 0.05, 0.48; p = 0.001). Interestingly, participants reporting provider recommendations for CKD screening had lower odds of screening (AOR: 0.17, 95% CI: 0.04, 0.79; p = 0.024). Sociodemographic factors, viral load status, comorbidity, perceived adequacy of CKD information, and distance to screening facilities were not significantly associated with CKD screening. Conclusion CKD screening uptake among adults on ART was high, but screening was influenced by clinical and service factors. Higher CD4 counts and more frequent clinic attendance were associated with increased screening, while provider recommendations were paradoxically linked to lower screening, highlighting gaps in translating advice into action. Strengthening integrated, patient-centered approaches and ensuring systematic CKD screening across all patient groups is essential to optimize early detection and management of kidney disease in PLHIV.